The Impact of Electronic Health Records in Management of Chronic Diseases in Uganda: A Case Study of Kampala International Teaching Hospital. - Tusasiibwe, Ivan (Kabale University, 2024)
The research was based on studying the impact of Electronic Health Records (EHR) in the management of chronic diseases in Uganda. It was carried out at KIU teaching hospital and its objectives were: to investigate the relevancy of EHR in the management of chronic diseases and establish the attitude of clinicians and other health workers towards the use of EHR in the management of chronic diseases. identify the challenges affecting EHR in the management of chronic diseases and establish possible solutions to the challenges encountered by EHR in the management of chronic diseases at KIU Teaching Hospital. In this study, the researcher used mixed methods to get the required results. This involved both quantitative and qualitative research approaches to understand a research problem. Findings indicate that EHR helps to quickly deliver information in managing clients, helps to easily gauge performance as fast as required; and easy access to the information in preparation for eligibility of clients' transition to new drugs. The study also revealed challenges that affect Electronic Health Records include lack of enough data personnel that leads to delayed data entry; and entry of incomplete data, work overload, and unreliable data in the system that leads to treatment errors. According to these study findings, the researcher recommends that there should be employment of more trained personnel that will be responsible for the accuracy and timely entry of clients' data into the EHR system to avoid treatment errors and ensure that data cleaning is done regularly to eliminate data errors in the system.